Exploring the Significance of Storytelling and Retelling Activities in English Language Learning - Rifiyanti, Hafizah; Hidayat, Syamsu (Fakultas Sastra - Universitas Muslim Indonesia, 2024)
The study aims to explore the effectiveness of using storytelling and retelling methods in improving students' English comprehension and proficiency. Through this activity, students were given the opportunity to listen to the story